Analysis of Institutional Aspects of Operation and Maintenance of Micro Hydro Power Plant Case Study in Sumba Island - NTT - Riandy, Andy; Rarasati, Ayomi Dita; Riantini, Leni Sagita (Proceeding International Conference on Science and Engineering, 2021)
Abstract. One strategy is to support the government to increase Electrification Ratio by utilizing Renewable Energy amidst the limitations of The State Electricity Company (PLN – Perusahaan Listrik Negara) to reach outermost and remote rural locations. Sumba Island is one of the areas with the lowest Electrification Ratio but has abundant natural resources for the development of renewable energy power plants. One of the Renewable Energy potentials being developed on Sumba Island is a Micro Hydro Power Plant. Renewable Energy issues are not only in demand supply but also on the sustainability of operation and maintenance. Several villages with electrification programs using Renewable Energy have experienced problems in terms of sustainable operation and maintenance due to the lack of strong institutions that manage the plants that have been built. This research was developed to answer the problems that have been mentioned with the aim of identifying and analysing the aspects that drive the institutional performance of Micro Hydro Power Plant operation and maintenance in Sumba Island, NTT (Nusa Tenggara Timur) Province. The results of the research are important aspects in institutional determination and maintenance that will support the elements of forming a sustainable institutional pattern as input for all stakeholders, especially the government in order to increase the national Electrification Ratio.